S.JUMAǴULOVTÍŃ “QÍRÍQ JÍLDAN SOŃǴÍ BIR KÚN...” DRAMASÍNDA WATANSÚYIWSHILIK IDEYALARÍNÍŃ SÁWLELENIWI - Qudiyarova, R. (ILIM hám JÁMIYET, 2024)
In this article, we will talk about the skill of using images to increase the social activity of young people based on the patriotic ideas of S.Jumagulov, who is known for wonderful works in the field of dramaturgy in Karakalpak literature. The ideas of patriotism in S.Jumagulov’s dramatic works are one of the issues waiting to be researched in Karakalpak literature. In this article, we will talk about the dramatist’s ability to illuminate the characters in his dramatic works, the love of ά person for the homeland and artistic service through the work.